2017
DOI: 10.1186/s11671-017-1951-x
|View full text |Cite
|
Sign up to set email alerts
|

Simple Route to Obtain Nanostructured CeO2 Microspheres and CO Gas Sensing Performance

Abstract: In this work, nanostructured CeO2 microspheres with high surface area and mesoporosity were prepared by the coprecipitation method, in absence of a template. The reaction between cerium nitrate and concentrated formic acid produced cerium formate, at room temperature. Further, calcination at 300 °C yielded single-phase CeO2 microspheres, with a diameter in the range 0.5–2.6 μm, the surface of these microspheres is completely nanostructured (diameter about 30–90 nm). CeO2 microspheres were used to fabricate a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 47 publications
0
2
1
Order By: Relevance
“…After determining the working temperature, the resistance versus time (Figure ) behavior was studied at 400 °C, changing the atmosphere from vacuum to synthetic air (∼20% oxygen) and 50 mmHg of CO (99.99%). Particularly, a relatively fast response time of 5.5 s can be observed after CO exposure, slightly higher than the 2 s obtained with a sintered CeO 2 film at 950 °C but better than the 9 s reported by López-Mena et al with 300 °C-calcined films. The observed resistance decrease indicates an n-type semiconductor behavior of the doped material.…”
Section: Results and Discussioncontrasting
confidence: 52%
“…After determining the working temperature, the resistance versus time (Figure ) behavior was studied at 400 °C, changing the atmosphere from vacuum to synthetic air (∼20% oxygen) and 50 mmHg of CO (99.99%). Particularly, a relatively fast response time of 5.5 s can be observed after CO exposure, slightly higher than the 2 s obtained with a sintered CeO 2 film at 950 °C but better than the 9 s reported by López-Mena et al with 300 °C-calcined films. The observed resistance decrease indicates an n-type semiconductor behavior of the doped material.…”
Section: Results and Discussioncontrasting
confidence: 52%
“…With the development of industrialization, emission pollution is becoming increasingly serious, so different types of gas sensors have been widely studied [1][2][3][4][5][6][7]. SnO 2 as a n-type and environment-friendly semiconductor has been studied by many different researchers [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Cerium oxide (CeO 2 ) also called ceria is a promising compound for several technological applications mainly because its physical and chemical properties are easily modified through a control over the composition, type of structure, morphology, and size of the particles during its synthesis and process 1,2 . Some of the essential properties of this material are oxygen storage capacity, redox potential, thermal stability, chemical stability, low toxicity, electronic conductivity, and high oxygen mobility [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…These researchers concluded that vacuum promotes oxygen desorption on the CeO 2 nanoparticles surface, and that the electrons loss in the 4f state of cerium causes a reduction in electrical resistance. López-Mena et al 3 synthesized nanostructured CeO 2 microspheres by co-precipitation, testing their application in carbon monoxide detection. They obtained a response time of 9 s at 275 °C, for the 200 ppm CO detection at a 100 kHz frequency.…”
Section: Introductionmentioning
confidence: 99%